Pengamatan Penyakit pada Tanaman Pinang (Areca Catechu L.) di Desa Mandala Jaya Kecamatan Betara Kabupaten Tanjung Jabung Barat - Yuza Defitri (Universitas Batanghari Jambi, 2022)
Areca nut (Areca catechu L.) is one of the leading plantation commodities in Jambi Province which has high economic value and plays an important role as a source of foreign exchange for the country. Areca nut plants in Jambi Province are most widely located in Betara District, West Tanjung Jabung Regency. To increase the yield of areca nut, it is necessary to know the diseases that attack areca nut and the percentage of the disease attack. It is useful for disease control in areca nut. This study aims to find out about the main diseases that attack areca nut plants such as yellowing leaf spot, leaf blight, leaf red rust, root rot/base of stem, fruit rot, shoot rot, yellow leaves, foot rot, flower die back and fruit drop, and Bacterial leaf stripe. The research was conducted using the Simple Random Sampling method. Plant samples were taken randomly at the people's areca nut plantations in Mandala Jaya Village, Betara District. Observations were made by looking at the symptoms of the disease and calculating the percentage of plants affected by the disease. Samples of areca nut plant parts that were attacked by the disease were identified at the Unbari Basic Laboratory.The research that has been conducted in Mandala Jaya Village, Betara District, Tanjung Jabung Barat Regency, it can be concluded that three main diseases were found in areca nut, namely yellowing leaf spot caused by the fungus Curvularia sp, leaf blight disease caused by the Pestalotia palmarum fungus and red rust leaf disease caused by the fungus Cephaleuros sp. The percentage of disease attacks, namely, yellow leaf spot disease (Curvularia sp.) was highest on P1 land by 40%, the highest percentage of Leaft Blight disease was found in P1 area at 35% and the highest percentage of red rust leaf disease was found in P1 area, which was 20%.